2019
DOI: 10.1007/978-3-030-18305-9_38
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Unsupervised Pretraining with External Knowledge for Natural Language Inference

Abstract: While recent research on natural language inference has considerably benefited from large annotated datasets (Williams et al., 2017;Bowman et al., 2015), the amount of inferencerelated knowledge (including commonsense) provided in the annotated data is still rather limited. There have been two lines of approaches that can be used to further address the limitation: (1) unsupervised pretraining can leverage knowledge in much larger unstructured text data; (2) structured (often humancurated) knowledge has started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Neural models focusing solely on the textual information (Wang and Jiang 2016a;Yang et al 2019) explore the sentence representations of premise structure and max pooling layers. Match-LSTM (Wang and Jiang 2016a) and Decomposable Attention (Parikh et al 2016) learn crosssentence correlations using attention mechanisms, where the former uses a asymmetric network structure to learn premise-attended representation of the hypothesis, and the latter a symmetric attention, to decompose the problem into sub-problems.…”
Section: Related Workmentioning
confidence: 99%
“…Neural models focusing solely on the textual information (Wang and Jiang 2016a;Yang et al 2019) explore the sentence representations of premise structure and max pooling layers. Match-LSTM (Wang and Jiang 2016a) and Decomposable Attention (Parikh et al 2016) learn crosssentence correlations using attention mechanisms, where the former uses a asymmetric network structure to learn premise-attended representation of the hypothesis, and the latter a symmetric attention, to decompose the problem into sub-problems.…”
Section: Related Workmentioning
confidence: 99%
“…In COLIEE 2021, we have two relationships that need to be verified: entailment and non-entailment. Yang et al [27] showed that human-created knowledge can further complement the use of pre-training models, to achieve better NLI prediction. Based on the results of Yang et al [27], we have exploited the external knowledge of the Kadokawa thesaurus [28], to tackle Tasks 4 and 5.…”
Section: Statute Law Textual Entailmentmentioning
confidence: 99%
“…NLI (Dagan et al, 2005;Iftene and Balahur-Dobrescu, 2007;MacCartney and Manning, 2008;MacCartney and Manning, 2009;MacCartney, 2009;Angeli and Manning, 2014;Bowman et al, 2015), also known as recognizing textual entailment (RTE), aims to model the logical relationships between two sentences, e.g., as a binary (entailment vs. non-entailment) or three-way classification (entailment, contradiction, and neutral). Recently deep learning algorithms have been proposed (Bowman et al, 2015;Chen et al, 2017a;Chen et al, 2017b;Chen et al, 2017c;Chen et al, 2018;Peters et al, 2018;Yoon et al, 2018;Kiela et al, 2018;Talman et al, 2018;Yang et al, 2019;Devlin et al, 2019). In this paper we will describe and evaluate our neural natural logic models on NLI.…”
Section: Natural Language Inferencementioning
confidence: 99%